Profile of medical care costs in patients with amyotrophic lateral sclerosis in the Medicare programme and under commercial insurance. Issue 1 (2nd January 2018) - Meng, Lisa; Bian, Amy; Jordan, Scott; Wolff, Andrew; Shefner, Jeremy M.; Andrews, Jinsy
Abstract: Objective : To determine amyotrophic lateral sclerosis (ALS)-associated costs incurred by patients covered by Medicare and/or commercial insurance before, during and after diagnosis and provide cost details. Methods : Costs were calculated from the Medicare Standard Analytical File 5% sample claims data from Parts A and B from 2009, 2010 and 2011 for ALS Medicare patients aged ≥70 years (monthly costs) and ≥65 years (costs associated with disability milestones). Commercial insurance patients aged 18–63 years were selected based on the data provided in the Coordination of Benefits field from Truven MarketScan® in 2008–2010. Results : Monthly costs increased nine months before diagnosis, peaked during the index month (Medicare: 10, 398; commercial: 9354) and decreased but remained high post-index. Costs generally shifted from outpatient to inpatient and private nursing after diagnosis; prescriptions and durable medical equipment costs were much higher for commercial patients post-diagnosis. Patients appeared to progress to disability milestones more rapidly as their disease progressed in severity (14.4 months to non-invasive ventilation [NIV] vs. 16.6 months to hospice), and their costs increased accordingly (NIV: 58, 973 vs. hospice: 76, 179). Conclusions : For newly diagnosed ALS patients in the U.S., medical costs are substantial and increase rapidly and substantially with each disability milestone.